Identification of depression in women during pregnancy and the early postnatal period using the Whooley questions and the Edinburgh Postnatal Depression Scale: protocol for the Born and Bred in Yorkshire: PeriNatal Depression Diagnostic Accuracy (BaBY PaNDA) study. Issue 6 (13th June 2016) - Littlewood, Elizabeth; Ali, Shehzad; Ansell, Pat; Dyson, Lisa; Gascoyne, Samantha; Hewitt, Catherine; Keding, Ada; Mann, Rachel; McMillan, Dean; Morgan, Deborah; Swan, Kelly; Waterhouse, Bev; et al.
Abstract : Introduction: Perinatal depression is well recognised as a mental health condition but <50% of cases are identified by healthcare professionals in routine clinical practice. The Edinburgh Postnatal Depression Scale (EPDS) is often used to detect symptoms of postnatal depression in maternity and child services. The National Institute for Health and Care Excellence (NICE) recommends 2 'ultra-brief' case-finding questions (the Whooley questions) to aid identification of depression during the perinatal period, but this recommendation was made in the absence of any validation studies in a perinatal population. Limited research exists on the acceptability of these depression case-finding instruments and the cost-effectiveness of routine screening for perinatal depression. Methods and analysis: The diagnostic accuracy of the Whooley questions and the EPDS will be determined against a reference standard (the Client Interview Schedule—Revised) during pregnancy (around 20 weeks) and the early postnatal period (around 3–4 months post partum) in a sample of 379 women. Further outcome measures will assess a range of psychological comorbidities, health-related quality of life and resource utilisation. Women will be followed up 12 months postnatally. The sensitivity, specificity and predictive values of the Whooley questions and the EPDS will be calculated against the reference standard at 20 weeks pregnancy and 3–4 months post partum. Acceptability of the depression case-finding instruments to women and healthcare professionals will involve in-depth qualitative interviews. An existing decision analytic model will be adapted to determine the cost-effectiveness of routine screening for perinatal depression. Ethics and dissemination: This study is considered low risk for participants. Robust protocols will deal with cases where risk of depression, self-harm or suicide is identified. The protocol received favourable ethical opinion from the North East—York Research Ethics Committee (reference: 11/NE/0022). The study findings will be published in peer-reviewed journals and presented at relevant conferences.